Evaluation of strategies to control Fab light chain dimer during mammalian expression and purification: A universal one‐step process for purification of correctly assembled Fab. Issue 7 (12th March 2015) - Spooner, Jennifer; Keen, Jenny; Nayyar, Kalpana; Birkett, Neil; Bond, Nicholas; Bannister, David; Tigue, Natalie; Higazi, Daniel; Kemp, Benjamin; Vaughan, Tristan; Kippen, Alistair; Buchanan, Andrew
ABSTRACT Fabs are an important class of antibody fragment as both research reagents and therapeutic agents. There are a plethora of methods described for their recombinant expression and purification. However, these do not address the issue of excessive light chain production that forms light chain dimers nor do they describe a universal purification strategy. Light chain dimer impurities and the absence of a universal Fab purification strategy present persistent challenges for biotechnology applications using Fabs, particularly around the need for bespoke purification strategies. This study describes methods to address light chain dimer formation during Fab expression and identifies a novel CH1 affinity resin as a simple and efficient one‐step purification for correctly assembled Fab. Biotechnol. Bioeng. 2015;112: 1472–1477. © 2015 Wiley Periodicals, Inc.